On the Relationship between Equivalent Potential Temperature (theta-e) and Convective Rain over Nigeria and Togo - Michael C. Ochei (International Journal of Atmosphere, 2026)
Convective precipitation is a key feature of West Africa's climate, driven by the West African monsoon system. Accurate forecasting of convective storms is challenging but essential for disaster mitigation in the region. This study investigates the ability of using equivalent potential temperature (theta-e) for predicting convective rainfall events in West Africa. Theta-e combines the thermodynamic effects of moisture and temperature to represent total energy available for convection. Daily rainfall and meteorological data over 15 years (2003–2017) from Nigeria and Togo were analyzed. Theta-e was estimated and correlated to rainfall occurrences using linear regression. Results demonstrate coherent increasing theta-e trends over time across the region. Seasonal cycles show peak rainfall corresponding to reduced theta-e during rainy months. Correlation analyses find theta-e and convective rainfall are moderately to weakly inversely related on monthly scales. Daily time-series indicate lower theta-e values accompany major convective rainfall event. The study concludes that while theta-e shows skill for identifying convective condition in West Africa, relationships are complex and non-linear. Thresholds of 340–370 K seem most favourable for intense rainfall events. However, theta-e value must exceed 355K 2-3 days before strong convective rain is observed at a station. Incorporating theta-e alongside other stability parameters into forecast models could enhance early warnings for flooding, lightning, hail and thunderstorms events. Overall, theta-e shows the predictive ability of using it as a parameter for characterizing environments conducive to severe convective rainfall development across West Africa.
Keywords: Equivalent potential temperature; abuja; convective rain; dapaong; lagos; lome